TEORI KEADILAN DALAM PERLINDUNGAN HUKUM BAGI KEPALA DESA DALAM MELAKSANAKAN KEBIJAKAN DESA ( Studi Kasus putusan perkara Nomor 66/Pid.Sus/Tpk/2015/PN. Sby ) - Muhammad Mashuri (universitas islam darul ulum lamongan, 2017)
The village is the lowest organizational structure of government in Indonesia. The formation of political society in Indonesia originated from the village. In running the organization of village government, the village is led by the village head and assisted by the village apparatus. In the structure of the Indonesian governmental organization, the village head includes government officials, in this case the elected village government is based on direct election by the village community with a six-year tenure. The role of the village head is very important in the level of government in Indonesia, because the village policy that will control a government in the region is prosperous or not. With the existence of Article 26 paragraph (3) of Law Number 6 Year 2014 regarding the Village, the legal norm of the Village Head in implementing his policy has been given legal protection that can be used as a basis for seeking justice when dealing with law enforcers. However, philosophically, the legal protection for the Village Head itself must be set forth in a separate legislation, so in implementing its policy, the Village Head feels more confident with the legal certainty of their fate in leading a Village Government so that it will not affect the development and village empowerment.